Hsa_circ_0020397 regulates colorectal cancer cell viability, apoptosis and invasion by promoting the expression of the miR‐138 targets TERT and PD‐L1 - Zhang, Xiu‐li; Xu, Ling‐ling; Wang, Fang (Cell biology international, 2017)
Colorectal cancer (CRC) is a common human gastrointestinal cancer, and recent studies indicate that circular RNA (circRNA) may regulate cancer development. In this study, we assess the role of circRNA specifically in colorectal cancer. Our quantitative PCR assays demonstrate an upregulation of the circRNA has_circ_0020397 and a downregulation of miR‐138 in CRC cells, as well as a negative correlation between these two. Using a dual‐luciferase reporter assay, we show evidence of miR‐138‐binding sites on hsa_circ_0020397, and that overexpression of hsa_circ_0020397 could inhibit the downregulation of luciferase activity by miR‐138. Although hsa_circ_0020397 did not influence miR‐138 expression per se, has_circ_0020397 did inhibit miR‐138 activity, as examined via the expression of miR‐138 targets telomerase reverse transcriptase (TERT) and programmed death‐ligand 1 (PD‐L1). Control treatments with plasmids overexpressing linear hsa_circ_0020397 did not have these effects. Hsa_circ_0020397 promoted cell viability and invasion of CRC cells and inhibited their apoptosis, whereas miR‐138 had the opposite effect. Nevertheless, hsa_circ_0020397 antagonized miR‐138 suppression of cell growth. When TERT or PD‐L1 expression was suppressed with siRNAs, the above functions of hsa_circ_0020397 were attenuated, suggesting that hsa_circ_0020397 can regulate CRC cell viability, apoptosis and invasion by promoting the expression of miR‐138 target genes. These findings support the role of circRNA in CRC pathogenesis.